Nitrogen‐Doped Carbon Electrodes: Influence of Microstructure and Nitrogen Configuration on the Electrical Conductivity of Carbonized Polyacrylonitrile and Poly(ionic liquid) Blends. Issue 19 (1st September 2015) - Einert, Marcus; Wessel, Claas; Badaczewski, Felix; Leichtweiß, Thomas; Eufinger, Christine; Janek, Jürgen; Yuan, Jiayin; Antonietti, Markus; Smarsly, Bernd M.
<x xml:space="preserve">Abstract</x> In this paper, the preparation of nitrogen‐doped carbon fibers and thin films from mixtures of polyacrylonitrile (PAN) and a poly(ionic liquid) (PIL) by electrospinning and dip‐coating is presented, respectively, followed by carbonization at distinct temperatures. The poor processability of the PIL into sub‐micrometer fibers by electrospinning—originating from its high charge density and meanwhile low glass transition temperature—is successfully circumvented by using blends of PAN and PIL. The electrospun fiber mats exhibit a high surface‐to‐volume‐ratio with an intrinsically macroporous through‐pore structure and a uniform fiber diameter after carbonization. Physicochemical characterization of the N‐doped carbons by means of scanning electron microscopy, algorithmic X‐Ray diffraction analysis, nitrogen physisorption, thermogravimetry, elemental analysis, energy‐dispersive X‐ray, and X‐ray photoelectron spectroscopy gives insight into their physical and electrical structures. Impedance measurements on carbonized PIL/PAN‐blends reveal high electrical conductivities up to 320 S cm−1, which are attributed to the incorporation of predominantly quaternary‐graphitic nitrogen atoms into the carbon network during carbonization. The results indicate that the electrical conductance of the N‐doped carbons strongly depends on the chemical environment of the inserted nitrogen atoms, the microstructural evolution of π‐conjugated carbon network—which in turn correlate with the carbonization temperature—and the chemical composition.